The bullet journal method : track your past, order your present, plan your future - Carroll, Ryder (London : Fourth Estate, 2021)
The Bullet Journal Method is a revolutionary organizational system that can transform your life in countless ways. Created by Ryder Carroll, this simple yet effective method uses a pen and paper to help you track your past, order your present, and plan your future. By combining elements of a wishlist, a to-do list, and a diary, the Bullet Journal allows you to get your thoughts out of your head and onto paper, where you can see them clearly and decide what to do about them. This helps you identify what matters and set goals accordingly, breaking down long-term goals into small actionable steps that you can work on consistently. Beyond time management, the Bullet Journal is also a manifesto for intentional living, encouraging you to align your beliefs and actions. Whether you're already a Bullet Journal user or just starting out, this book offers valuable insights and exercises to help you live a more calm, focused, and purposeful life.
Includes index.
Keywords: Tracking the past; Ordering the present; Designing the future